Early intravenous beta-blockers in patients undergoing primary percutaneous coronary intervention for ST-segment elevation myocardial infarction: A patient-pooled meta-analysis of randomized clinical trials. Issue 5 (1st August 2020) - Hoedemaker, Niels PG; Roolvink, Vincent; de Winter, Robbert J; van Royen, Niels; Fuster, Valentin; García-Ruiz, José M; Er, Fikret; Gassanov, Natig; Hanada, Kenji; Okumura, Ken; Ibáñez, Borja; van 't Hof, Arnoud W; et al.
Abstract : Background: Conflicting evidence is available on the efficacy and safety of early intravenous beta-blockers before primary percutaneous coronary intervention for ST-segment elevation myocardial infarction. We performed a patient-pooled meta-analysis of trials comparing early intravenous beta-blockers with placebo or routine care in ST-segment elevation myocardial infarction patients undergoing primary percutaneous coronary intervention. Aim: The aim of this study was to evaluate the clinical and safety outcomes of intravenous beta-blockers in ST-segment elevation myocardial infarction patients undergoing primary percutaneous coronary intervention. Methods: Four randomized trials with a total of 1150 patients were included. The main outcome was one-year death or myocardial infarction. Secondary outcomes included biomarker-based infarct size, left ventricular ejection fraction during follow-up, ventricular tachycardia, and a composite safety outcome (cardiogenic shock, symptomatic bradycardia, or hypotension) during hospitalization. Results: One-year death or myocardial infarction was similar among beta-blocker (4.2%) and control patients (4.4%) (hazard ratio: 0.96 (95% confidence interval: 0.53–1.75, p =0.90, I 2 =0%). No difference was observed in biomarker-based infarct size. One-month left ventricular ejection fraction was similar, but left ventricular ejection fraction at six months was significantly higher in patients treated with early intravenous beta-blockade (52.8% versus 50.0% in the control group, p =0.03). No difference was observed in the composite safety outcome or ventricular tachycardia during hospitalization. Conclusion: In ST-segment elevation myocardial infarction patients undergoing primary percutaneous coronary intervention, the administration of early intravenous beta-blockers was safe. However, there was no difference in the main outcome of one-year death or myocardial infarction with early intravenous beta-blockers. A larger clinical trial is warranted to confirm the definitive efficacy of early intravenous beta-blockers.